Numerical Investigation on Behavior of Compressive Piles in Coastal Tidal Flat with Fill - Kanmin Shen; Kuanjun Wang; Juntian Yao; Jian Yu (Journal of Marine Science and Engineering, 2022)
The control centers of wind power plants are usually located in coastal tidal flat areas. A thick fill should be placed at the original ground level to ensure that the design elevation of the control centers is maintained above the water table. However, the filling would cause a long-term ground settlement and further lead to the development of the negative skin friction (NSF) of the pile foundations for the control centers. The CPTU tests were conducted to calibrate the soil properties, of which the rationalities were verified by comparisons of the pile-bearing capacities between the full-scale axial compressive tests and β-method. The numerical analysis method was then established to investigate the influence of additional ground pressures on the pile axial bearing behavior over time and the influence of NSF caused by consolidation on pile-bearing capacity. Finally, a simple procedure was further employed to investigate the evolution of the long-term pile-bearing behavior.